Exploring Individual Experiences in Understanding Environmental Policies: A Phenomenological Approach to Urban Communities - Ayub Kasim; Irman Halid; Asriana Abdullah; Ince Rahmah Ismail (Postgraduate, University of Mataram, 2025)
Environmental policy has long been a central topic in sustainability studies, with a growing body of research emphasizing its social and psychological dimensions. However, much of the existing literature predominantly relies on quantitative measures to assess public attitudes, often overlooking the subjective experiences that shape individuals' perceptions of environmental policies. This research aims to address this gap by exploring how individuals interpret and make meaning of environmental policies in their everyday lives. Here, we adopt a phenomenological approach to capture the lived experiences and personal meanings attached to these policies. Through in-depth interviews with participants, we uncover the complex ways in which personal experiences, social norms, and cultural values influence people's perceptions and actions regarding environmental policies. Our findings reveal that subjective experiences, rather than mere awareness or factual knowledge, play a significant role in shaping environmental behavior. These results underscore the importance of considering personal narratives in environmental policy formulation and open new avenues for future research that explores the intersection of personal experience and policy acceptance.